Land Tenure and Legal Pluralism in Africa and Asia: Gender, Reform, and Recognition - Sutikno, Aldilla Yulia Wielys (Legalis : Journal of Law Review, 2024)
This narrative review examines the interplay between customary land rights and statutory legal frameworks within plural legal systems, with a focus on land tenure security in sub-Saharan Africa and Southeast Asia. The objective is to assess how pluralism in land law affects the recognition and protection of customary land rights, particularly among marginalized communities. A systematic literature search was conducted using databases such as Scopus, Google Scholar, and PubMed. Keywords including "tenure security," "customary land rights," "land reform," "legal pluralism," and "community participation" guided the review. Inclusion criteria focused on empirical studies addressing policy impacts, gender dynamics, and community-based land governance. The results reveal that customary law plays a crucial role in ensuring tenure security, especially where formal systems are weak or exclusionary. In Ghana and Tanzania, customary tenure supports collective land stewardship and sustains agricultural livelihoods. However, legal ambiguities and inconsistent state recognition often render these systems vulnerable. Gender disparities remain pronounced, with women frequently excluded from land decision-making despite reform initiatives. Comparative insights from Kenya and Uganda underscore the challenges of harmonizing plural systems without undermining local autonomy. The discussion highlights the need for inclusive legal reforms, participatory documentation mechanisms, and targeted interventions to empower underrepresented stakeholders. The findings emphasize that integrating customary law into statutory systems and strengthening community roles in land governance are essential for achieving equitable, secure, and sustainable land rights. Future research should evaluate the effectiveness of such integrative frameworks across jurisdictions and explore models that reconcile legal diversity with development goals.